2013
DOI: 10.4161/epi.24710
|View full text |Cite
|
Sign up to set email alerts
|

HDAC turnover, CtIP acetylation and dysregulated DNA damage signaling in colon cancer cells treated with sulforaphane and related dietary isothiocyanates

Abstract: Histone deacetylases (HDACs) and acetyltransferases have important roles in the regulation of protein acetylation, chromatin dynamics and the DNA damage response. Here, we show in human colon cancer cells that dietary isothiocyanates (ITCs) inhibit HDAC activity and increase HDAC protein turnover with the potency proportional to alkyl chain length, i.e., AITC < sulforaphane (SFN) < 6-SFN < 9-SFN. Molecular docking studies provided insights into the interactions of ITC metabolites with HDAC3, implicating the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(140 citation statements)
references
References 47 publications
8
132
0
Order By: Relevance
“…SFN has previously been shown to inhibit histone deacetylase activity (18,45,56). In human volunteers, a single ingestion of a small amount of broccoli sprouts (ϳ70 g), which contain particularly high amounts of SFN, inhibits histone deacetylase activity in circulating peripheral blood mononuclear cells and consequently induces histone H3 and H4 acetylation a few hours after intake (56).…”
Section: Discussionmentioning
confidence: 99%
“…SFN has previously been shown to inhibit histone deacetylase activity (18,45,56). In human volunteers, a single ingestion of a small amount of broccoli sprouts (ϳ70 g), which contain particularly high amounts of SFN, inhibits histone deacetylase activity in circulating peripheral blood mononuclear cells and consequently induces histone H3 and H4 acetylation a few hours after intake (56).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, autophagy targets the DNA damage repair protein Sae2 (orthologous to human RBBP8) for autophagic degradation upon its acetylation, 28 and autophagy has also been implicated in regulating levels of RBBP8 in human colon cancer cells. 29 These data suggest that autophagy may control DNA damage repair in mammalian cells through the regulation of RBBP8, a key protein mediating the choice between nonhomologous and homologous repair pathways. 49 Autophagy has also been shown to influence cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies showed that autophagy promotes genome stability by maintaining cellular metabolic homeostasis, 27 and more recent work in yeast and mammalian cells suggests that autophagy directly influences DNA damage repair by modulating levels of the key repair protein RBBP8/ CtIP. 28,29 Moreover, autophagy guards against aneuploidy by regulating cell cycle progression and cytokinesis. 30,31 In light of these emerging roles for autophagy in senescence and genome instability, 2 critical sequelae of telomere dysfunction, we sought to delineate the potential functions of autophagy in the cellular response to acute telomere dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Studies involved in the evaluation of sulforaphane as an HDAC inhibitor, and those aimed at providing insights into the mechanisms associated with sulforaphane-regulated inhibition of HDAC activity, have focused on the roles of HDAC3 and HDAC6 as important targets (43, 89,223,224). After the incubation of HCT116 human colon cancer cells with 15 lM sulforaphane, a significant reduction in HDAC1, HDAC2, HDAC3, and HDAC8 was observed compared with vehicle-treated cells at 36 h post administration (223).…”
mentioning
confidence: 99%